Dermoscopic features of mucosal lichen planus. (3rd June 2021) - Rouai, Meriem; Litaiem, Noureddine; Hammami, Houda; Bacha, Takwa; Jones, Meriem; Ksontini, Meriem; Rammeh, Soumaya; Mokni, Mourad; Zeglaoui, Faten
Abstract: Background: Lichen planus (LP) is a chronic inflammatory dermatosis that affects the skin and the mucous membranes. The literature on the dermoscopic aspects of mucosal LP is still scarce. This study aimed to describe the dermoscopic aspects of mucosal LP and to provide a comprehensive updated summary of the literature. Methods: This was a cross‐sectional, multicenter study conducted in Charles Nicolle, La Rabta, and Habib Thameur hospitals from December 2019 to October 2020. We included patients with histologically confirmed mucosal LP for whom a dermoscopic examination was performed. Results: Twenty‐seven patients were enrolled. The main dermoscopic structures observed were as follows: Wickham's striae (WS) (91%), vessels (88%), pigmentated structures (41%), erosions (63%), scales (34%), and blunting of lingual papillae (3.1%). WS patterns were as follows: reticular (67%), radial (48%), annular (30%), globular (15%), dotted/starry sky (15%), and veil‐like blue or grey‐white homogenous pattern (19%). Vascular structures were as follows: linear (85%), dotted (70%), looped (22%), and peripheral sea anemone‐like vessels (37%). These vessels were distributed in a radial arrangement at the periphery of the lesions in 67% of the cases. Pigmented structures included brown/blue globules (33%), grey‐blue dots (30%), and brown dots (26%). Conclusion: Dermoscopic features of mucosal LP are varied. WS is the hallmark of LP. The distribution and aspects of WS in mucosal LP were slightly different from those described in cutaneous LP. Physicians should be aware of these dermoscopic features that could help differentiate LP from other mucosal inflammatory diseases.